2019
DOI: 10.3233/jnd-190403
|View full text |Cite
|
Sign up to set email alerts
|

AVXS-101 (Onasemnogene Abeparvovec) for SMA1: Comparative Study with a Prospective Natural History Cohort

Abstract: Background: Spinal muscular atrophy type 1 (SMA1) is the leading genetic cause of infant mortality for which therapies, including AVXS-101 (onasemnogene abeparvovec, Zolgensma ® ) gene replacement therapy, are emerging. Objective: This study evaluated the effectiveness of AVXS-101 in infants with spinal muscular atrophy type 1 (SMA1) compared with a prospective natural history cohort and a cohort of healthy infants. Methods: Twelve SMA1 infants received the proposed therapeutic dose of AVXS-101 (NCT02122952). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 22 publications
(49 reference statements)
4
131
0
12
Order By: Relevance
“…However, for sure, for the production of other viral vectors, such as AAV, larger bioreactors are needed, as the required viral vector numbers per patient are often higher compared to lentiviral vectors. 8,37,38 Adenoviral vector production in iCELLis Nano and scale-X bioreactors…”
Section: Lentiviral Vector Yields In Icellis Nano and Scale-x Bioreacmentioning
confidence: 99%
“…However, for sure, for the production of other viral vectors, such as AAV, larger bioreactors are needed, as the required viral vector numbers per patient are often higher compared to lentiviral vectors. 8,37,38 Adenoviral vector production in iCELLis Nano and scale-X bioreactors…”
Section: Lentiviral Vector Yields In Icellis Nano and Scale-x Bioreacmentioning
confidence: 99%
“…15 However, correlation was based on two infants who had very high baseline function at 1 month of age, who are not representative of the population of postsymptomatically identified patients. 16,17 SMN2 copy number was not significantly correlated with attainment of the sitting position. Although three copies of SMN2 are not associated with a better prognosis in patients with symptomatic SMA1 treated with nusinersen, 6,8,9 preliminary results from a study of infants treated presymptomatically with nusinersen indicated that patients with three SMN2 copies have better improvement than patients with two copies.…”
Section: Discussionmentioning
confidence: 74%
“…In the clinical trial of the gene therapy onasemnogene abeparvovec, the baseline CHOP‐INTEND score in conjunction with age was demonstrated to be a strong predictive factor of walking acquisition . However, correlation was based on two infants who had very high baseline function at 1 month of age, who are not representative of the population of postsymptomatically identified patients …”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, because muscle cells are non-dividing and long-lived, there is potential that a one-time treatment could have long-term and perhaps even life-long benefits. In fact, preclinical and clinical studies in neuromuscular diseases to date indicate no loss in durability [25,[52][53][54][55]. The objective of gene therapy for DMD is to deliver a gene encoding a functional version of dystrophin systemically to all target tissues involved in DMD pathology and thereby ameliorate the progression of the disease.…”
Section: Special Considerations For Dmd Gene Therapymentioning
confidence: 99%
“…Clinical research on gene transfer therapy has demonstrated positive outcomes including improvements in muscle function, developmental milestones, and survival in spinal muscular atrophy [22]; restoration of vision in patients who were blind; eradication of blood cancers for patients not responding to other treatments; correction of hemoglobinopathies and coagulation factor deficiencies; and immune system restoration in children born with primary immune deficiency [19,23,24]. Notably, many clinical studies report successful results with gene therapy agents in pediatric patients [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%